59th Open Seminar on Acoustics Boszkowo, Poland, September 10 – 14, 2012 - JÓZEFCZAK, Arkadiusz (Archives of Acoustics, 2012)
The Scientific and Organizing Committees of 59thOpen Seminar on Acoustics would like to present theabstracts of papers submitted for this conference. TheOpen Seminar on Acoustics (OSA) is an annual confer-ence, the largest in the country which has been bring-ing Polish acousticians together for nearly sixty years.It is organized sequentially by different departments ofPolish Acoustical Society (PTA) – in 2012 by the Poz-nań Division. The conference presents all sections ofacoustics, such as: physical acoustics, technical acous-tics, environmental acoustics, speech acoustics, hear-ing acoustics, musical acoustics, architectural acous-tics, etc. The aim of the conference is to exchange sci-entific experience in the field of acoustics, promote sci-ence and integrate specialists from various fields. Theintegration of Polish acousticians is extremely impor-tant because of the interdisciplinary nature of acous-tics as a science. This allows the exchange of ideas,research methods and possibilities of application usedby researchers and practitioners the many branches ofacoustics.